2018
DOI: 10.1002/adma.201704652
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing Bioinspired Antifogging Materials with Superwettability: Progresses and Challenges

Abstract: Antifogging (AF) structure materials found in nature have great potential for enabling novel and emerging products and technologies to facilitate the daily life of human societies, attracting enormous research interests owing to their potential applications in display devices, traffics, agricultural greenhouse, food packaging, solar products, and other fields. The outstanding performance of biological AF surfaces encourages the rapid development and wide application of new AF materials. In fact, AF properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
120
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 291 publications
(603 reference statements)
1
120
0
Order By: Relevance
“…Long before human had even arisen in the world, the evolving life had developed countless strategies to actively manipulate liquids for surviving . The lotus leaves in ponds exhibit highly water repellence and self‐cleaning capability .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long before human had even arisen in the world, the evolving life had developed countless strategies to actively manipulate liquids for surviving . The lotus leaves in ponds exhibit highly water repellence and self‐cleaning capability .…”
Section: Introductionmentioning
confidence: 99%
“…Although enormous works have been reported in this field, controlled liquid manipulation through engineered micro‐/nanostructure, especially that rivals those of biological systems, remains a challenge, which usually involves certain trails and error processes. Therefore, a comprehensive understanding about the relationship between liquid manipulation and micro‐/nanostructured interface is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Good performance of such AFF coatings on glass and metals (Al and Cu) has been achieved. This phenomenon is known as fogging or frosting depending on whether the surface temperature is lower than the dew or frost point of water.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the self‐healing function also displays great promise in surfaces with special functions. The extensive studies have been reported for designing special surface for controlling wettability, antifouling, antifogging, and so forth, which can be called “functional surface” or “functional surface material,” attracting enormous interests owing to their potential applications in different fields. Typically, the most well‐known fascinating surface property present in nature is lotus leaf effect, which remains self‐cleaning despite in mud, a real mystery of superhydrophobic property.…”
Section: Introductionmentioning
confidence: 99%